Entrepreneurship and family business - Stewart, Alex, 1950-; Lumpkin, G. T.; Katz, Jerome A. (Bingley : Emerald, 2010)
Volume 12 will consider the timely issue of entrepreneurship and family business. Papers consider the issues, problems, contexts, or processes that make a family firm more entrepreneurial. A representative, but by no means exhaustive, listing of relevant topics includes: the emergence and growth of family businesses; founding conditions unique to family firms; maintaining the entrepreneurial spirit of the founding generation; the role of family in corporate entrepreneurship; the use of entrepreneurial policies, practices and strategies by family firms; outcomes attributable to differences between more and less entrepreneurial family firms; family firm versus non-family firm approaches to entrepreneurial decision making; entrepreneurial characteristics and practices across the generations of a family firm; entrepreneurship as an avenue to strategically renew family firms; the allocation of family-based resources to entrepreneurial endeavors.
An introduction to the special volume on family business and entrepreneurship / Alex Stewart, G.T. Lumpkin, Jerome A. Katz -- The importance of looking toward the future and building on the past: entrepreneurial risk taking and image in family firms / Esra Memili, Kimberly A. Eddleston, Thomas M. Zellweger, Franz W. Kellermanns and Tim Barnett -- Understanding exit from the founder's business in family firms / Carlo Salvato, Francesco Chirico and Pramodita Sharma -- The role of family member support in entrepreneurial entry, continuance, and exit: an autoethnography / William R. Meek -- Spousal context during the venture creation process / Sharon M. Danes, Amanda E. Matzek and James D. Werbel -- Society in embryo: family relationships as the basis for social capital in family firms / Ritch L. Sorenson, G. T. Lumpkin, Andy Yu and Keith H. Brigham -- The catholic spirit and family business: contrasting Latin America, Eastern Europe, and Southern Europe / Vipin Gupta and Nancy Levenburg -- Skeptical about family business: advancing the field in its scholarship, relevance, and academic role / Alex Stewart -- The yin and yang of kinship and business: complementary or contradictory forces? (and can we really say?) / Alex Stewart and Michael A. Hitt -- Kinship, capital, and the unsettling of assumptions: contemporary anthropology and the study of family enterprise and entrepreneurship / Danilyn Rutherford -- Kinship and gender / Harold W. Scheffler -- Sources of entrepreneurial discretion in kinship systems / Alex Stewart -- Cross campus collaboration: a law school perspective / Edward A. Fallone -- The promise of family business as an academic field in major research universities / Anne S. Miner -- Practice-based research in family business / Dean R. Fowler and Debra Houden -- Four aesthetic models for relevant research in the field of family enterprise / Judy Green -- Team approaches to entrepreneurship and family business education / Frank Hoy -- Late stage entrepren
Description based on print version record.
Includes bibliographical references.
Print version record
Keywords: Family-owned business enterprises; Entrepreneurship; Entrepreneurship; Employee-ownership & co-operatives.; Business & Economics -- Entrepreneurship; Business & Economics -- Small Business; Business & Economics -- New Business Enterprises